DEPRECIATION AND VALUATION FOR A UTILITY WITH ONLY ONE PLANT. - Krebs, William S. (The Accounting Review, 1958)
Abstract A heated controversy is continually waged over the relationship of depreciation to the rate base. Difficult and controversial as is the issue for large and typical utilities, it is especially troublesome for small utilities, and the literature is noticeably lacking in this field. To help clarify objective thinking along these lines, it is proposed to take, as an illustration, a utility with only one plant and to enunciate the principles applicable to small and large organizations as well. This article presents a discussion of the method of determining the size and type of the rate base, comments on how to arrive at the rate of return equitable to all parties, on what part depreciation plays in the accounts and in the rate base and on some elementary aspects of utility financial structure as they relate to the topic. What seems to be a logical program has been brought to the front as all the various phases of the subject have been considered. It is not to be expected that the controversy will die down, but, nevertheless, it was essential to face all the issues squarely and not to avoid even the most controversial aspects of the whole question. The seriousness of inflation as it reaches out to touch utility regulation cannot be overemphasized.